Mapping Pectic-Polysaccharide Epitopes in Cell Walls of Forage Chicory (Cichorium intybus) Leaves - Xuezhao Sun (Frontiers Media S.A., 2021)
The cell walls of forage chicory (Cichorium intybus) leaves are known to contain high proportions of pectic polysaccharides. However, little is known about the distribution of pectic polysaacharides among walls of different cell types/tissues and within walls. In this study, immunolabelling with four monoclonal antibodies was used to map the distribution of pectic polysaccharides in the cell walls of the laminae and midribs of these leaves. The antibodies JIM5 and JIM7 are specific for partially methyl-esterified homogalacturonans; LM5 and LM6 are specific for (1→4)-β-galactan and (1→5)-α-arabinan side chains, respectively, of rhamnogalacturonan I. All four antibodies labelled the walls of the epidermal cells with different intensities. JIM5 and JIM7, but not LM5 or LM6, labelled the middle lamella, tricellular junctions, and the corners of intercellular spaces of ground, xylem and phloem parenchyma. LM5, but not LM6, strongly labelled the walls of the few sclerenchyma fibres in the phloem of the midrib and lamina vascular bundles. The LM5 epitope was absent from some phloem parenchyma cells. LM6, but not LM5, strongly labelled the walls of the stomatal guard cells. The differential distribution of pectic epitopes among walls of different cell types and within walls may reflect the deposition and modification of these polysaccharides which are involved in cell wall properties and cell development.